Partially Dehydrated Castor Oil-Based Isoalkyl and Polyol Esters as Potential Base Stocks for Industrial Applications - Azmeera, Thirupathi; Punyamurthy, Rajini; Karuna, M.S.L.; Vidavalur, Siddaiah; Madhu, Devarapaga (Asian Journal of Chemistry, 2022)
Partially dehydrated castor oil (PDCO) which is of less use in the paint and furniture coating formulations has been modified to develop biolubricant base stocks. PDCO (44.1%, non-conjugated linoleic acid; 32%, conjugated linoleic acid (18:2) isomers and 15.3% ricinoleic acid) obtained from a local industry was hydrolyzed under alkaline conditions. The fatty acids obtained (PDCFAs) in 98% yields were reacted with polyols namely 2-ethyl hexanol, neopentyl glycol, trimethylol propyl, pentaerythritol to obtain respective isoalkyl erters and esters of polyol with >95% yield. The base stocks exhibited very high viscosity indices (187.288 to 187.687), excellent pour point (-25 to -40 ºC) and high flash points (212 to 317 ºC) required for a variety of industrial applications namely metal working, hydraulic, forging, cutting fluid, gear oil applications. The tribological properties of PDCO, exhibited very low WSD (0.72-0.79 mm) and WSVs (0.82-0.83 mm3) with high load carrying capacities (180-220 kg) indicating low friction and less energy losses between the sliding surfaces. This was also accompanied by very high thermo-oxidation stabilities [Oxidation stability (230-242 ºC); Onset temperature (300-381 ºC)] of the base stacks due to branching. Overall all the PDCO isoalkyl and polyol esters exhibited excellent properties suitable for a wide range of industrial applications on par with mineral oil based lubricants.